Pengaruh Digital Marketing dan Customer Relationship Management Digital dalam Meningkatkan Pemasaran Produk Telur di X Kabupaten Pacitan - Rizal Rifai; Agus Suyatno; R. Taufik Nur Muftiyanto (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2025)
This study is driven by the importance of adopting digital-based marketing strategies in the agribusiness sector, particularly in rural areas such as Pacitan Regency. Y, as a local egg farming enterprise, seeks to enhance its marketing effectiveness through the implementation of Digital Marketing and digital customer relationship management (CRM). The objective of this study is to examine the influence of these two strategies on egg product marketing. This research employed a quantitative correlational approach, with data collected through questionnaires and interviews. The sample consisted of 97 respondents who are consumers of Y. The results show that both Digital Marketing and digital CRM simultaneously have a significant effect on improving product marketing. Digital Marketing plays a role in expanding reach and product appeal by utilizing online platforms and targeted advertising, which helps increase product visibility to a broader audience. Meanwhile, digital CRM is effective in building long-term relationships and customer loyalty by providing personalized services, improving customer engagement, and maintaining communication. These findings imply that the integration of both strategies is highly relevant for micro-enterprises to improve competitiveness in the digital era, as they allow businesses to reach a wider market while fostering strong customer connections. This study also contributes to the development of literature on digital agribusiness marketing and serves as a practical reference for business promotion strategies, especially for small-scale enterprises looking to leverage digital tools for growth.